Anticorruption in Transition 2 : Corruption in Enterprise-State Interactions in Europe and Central Asia 1999-2002. - Gray, Cheryl Williamson, 1954- (World Bank e-Library., 2004)
"Controlling corruption is an essential part of good governance and poverty reduction, and it poses an enormous challenge for governments all around the world. This report analyzes patterns and trends in corruption in business-government interactions in the transition economies of Central and Eastern Europe and the former Soviet Union. It points to some encouraging signs that the magnitude and negative impact that corruption exerts on businesses may be declining in many countries in the region. It also shows how some types of firms - most notably small private ones - encounter more corruption than others, and its underscores the importance of policy and institutional reforms in achieving long-term success in the fight against corruption. The longer-term sustainability of recent improvements is not certain, however, and the challenges ahead remain formidable."--Jacket